Agricultural value chain finance in Indonesia: Executive summary - de Brauw, Alan; Sayaka, Bambang; Pasaribu, Sahat; Ambler, Kate; Herskowitz, Sylvan; Suryani, Erma (International Food Policy Research Institute, 2020)
This report describes the present state of agricultural value chain finance in Indonesia and suggests policies that could help expand its availability where formal financial services have been unable to meet value chain actors’ needs. We first consider the features of a policy environment needed for agricultural value chain finance to flourish. Key points related to the policy environment are: Allow interest rates for loans from the formal sector to be priced by the market; Support secure, inclusive payment systems and transaction frameworks; Develop a legal framework that supports both the use of movable collateral in loans and a warehouse receipts system; Develop a legal and/or regulatory framework that supports contract farming among smallholders; And allow for a more open, technology-driven financial architecture that facilitates market entry among nontraditional financial service providers.